Somalia : Second and Third Reviews Under the Extended Credit Facility Arrangement and Request for Modification of Performance Criterion, Modification of Performance Criteria, Interim Assistance and Rephasing of Access and Extension of the Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Somalia. (IMF Staff Country Reports; Country Report ;, 2022)
Notwithstanding multiple shocks-including COVID-19, drought, and surge in commodity prices-the Somali authorities have preserved macroeconomic stability and maintained the reform momentum, supported by use of the SDR allocation and cash balances. After some considerable delay, Parliamentary and Presidential elections were successfully completed, and President Mohamud was sworn in on May 15, 2022. The authorities have affirmed their commitment to the objectives and policies underpinning the program supported by the Extended Credit Facility and the HIPC process.